IMPLEMENTATION OF IOT TEMPERATURE AND HUMIDITY ON MOISTURE CONTENT VALUES IN NUTMEG SEED DRYERS USING ELECTRIC STOVES - Festo Andre Hardinsi; Mustari; Sofyan Sukwara Akfan; Christof Geraldi Simon (Universitas Muhammadiyah Metro, 2026)
Fakfak Regency is known as an abundant producer of nutmeg fruits and seeds and is dubbed the nutmeg city. However, there is a problem that often occurs in nutmeg farmers, namely, aflatoxin attacks. In addition, there are several obstacles for nutmeg farmers, namely declining processing time efficiency and declining productivity in nutmeg seed quality. Therefore, it is necessary to monitor the nutmeg drying process. The purpose of this study is to monitor the real-time process time, temperature, and humidity of the IoT nutmeg drying device on the moisture content. The method used in this study is design of a nutmeg seed dryer using an electric stove. The design uses an IoT monitoring implementation. Based on the SNI-01-0006-1993, the appropriate moisture content value in the nutmeg seed dryer is obtained by using an electric stove within 10 and 13 hours. The results of the 10-hour study showed a moisture content value of 9.77% and the results of IoT monitoring showed a temperature value of 54°C and a humidity of 78g/kg. And the results of the 13-hour study showed a moisture content value of 6.28% and the results of IoT monitoring showed a temperature value of 65°C and a humidity of 85g/kg.